Ethiopian food-based dietary guidelines: development, evaluation, and adherence monitoring - Bekele, Tesfaye Hailu (Wageningen University & Research, 2022)
Food-based dietary guidelines (FBDG) promote and maintain healthy eating in a population by providing country-specific guidance. However, many African countries like Ethiopia do not have FBDG. This thesis described the development and evaluation of Ethiopia's FBDG and healthy eating index (Et-HEI). The methodological framework for developing Ethiopian FBDG and a healthy eating index is described as a three-phase process. A multidisciplinary technical working group was established to develop FBDG for the general population above two years of age. Priority diet-related public health problems and risk factors and a systematic review of dietary patterns related to the identified priority health outcomes following a multi-step process. we reviewed systematic reviews and developed dietary recommendations for the Ethiopian FBDG. Systematic reviews were eligible if they investigated the impact of foods, food groups, diet, or dietary patterns on nutritional status (protein-energy, vitamin A, zinc, calcium, folate), cardiovascular diseases (CVD), or type 2 diabetes mellitus (T2DM). The results showed that not many studies on the impact of diet on protein-energy malnutrition or micronutrient deficiencies were published. Consumption of 30-90g of whole grains daily reduces the risk of CVD and T2DM. Consumption of 15-35g of nuts and seeds per day increases antioxidant levels such as vitamin E and A and lowers CVD and blood sugar levels. Pulse consumption of 50-150g per day or four servings (400g) per week reduces the incidence of CVD and T2DM. Milk and dairy foods are good sources of calcium and help improve bone mineral density among adults and children. Processed meat intake to less than 50 grams daily and eating more fish reduce CVD risk. Sugar consumption should be less than 5-10% of total energy daily to lower the risk of obesity, CVD, and T2DM. the association of saturated fatty acids with CVD and T2DM is inconclusive. CVD and T2DM risks are reduced by consuming 200-300 grams of vegetables and fruits daily. Plant-based diets lower the risk of CVD and T2DM and reduce micronutrient bioavailability. We studied the acceptability, cultural appropriateness, consumers' understanding, and practicality of the Ethiopian FBDG's messages, tips, and food graphics using focus group discussions and key informant interviews. Forty consumers, 15 high-level nutrition experts, 30 health extension workers (HEWs), and 15 agriculture extension workers (AEWs) participated to consider different stakeholder perspectives. The results indicated that most study participants were highly interested in implementing the dietary guidelines once these guidelines are officially released. Based on the participants' views, most messages align with the current nutrition education materials implemented in the country, except the messages about physical activity and alcohol intake. However, participants suggested defining technical terms such as ultra-processing, whole grain, and safe and balanced diet simpler for a better understanding. Practicality, affordability, availability, and access to the market were the major barriers reported for adherence to the guidelines. Findings showed that the dietary guidelines should address fasting and traditional cooking methods. A healthy diet was developed for Ethiopian women of reproductive age. Linear goal programming models were built for three scenarios (Model 1 or non-fasting, Model 2 or continuous fasting, and Model 3 or intermittent fasting) using two days of 24-hour dietary recall (24 HDR) as input dates. These data were collected from 494 Ethiopian women of reproductive age in November and December 2019. The model minimized a function of deviations from nutrient reference values. Women's mean energy intake was above 2000 kcal across sociodemographic characteristics. The amounts of milk and dairy foods (396 versus 30 g/day), nuts and seeds (20 versus 1 g/day), and fruits (200 versus 7 g/day) were higher in the modelled diets than in the current diet. Besides calcium and vitamin B12 in the continuous fasting diet, the proposed diets for Ethiopian women of reproductive age during non-fasting, continuous fasting, and intermittent fasting can provide an adequate intake of the targeted 11 micronutrients. The proposed diet had a maximum cost of 120 Ethiopian birr ($3.5) per day, which was twice the current diet's cost. The Et-HEI for estimating adherence to the 2022 Ethiopian FBDG was developed and evaluated in women of reproductive age. The Et-HEI consists of 11 components, classified as adequacy, moderation, or optimum, based on the evidence on diet-disease relationships and contribution to nutrient adequacy. Each component was scored between 0 and 10 points, and thus the total Et-HEI scored from 0 (minimum) to 110 (maximum) for utmost adherence to the FBDG. The Et-HEI score was evaluated against the Minimum Dietary Diversity score for Women (MDD-W), the probability of nutrient intake adequacy, and differences in sociodemographic characteristics of the women. The average Et-HEI score for women of reproductive age was 49 out of 110. A low MDD-W (3.5) was also reflected. Most women consumed grains, vegetables, legumes, fat and oils, and salt components. Due to low intake as recommended, almost all women received a score of 10 for sugar and alcohol consumption. Most women did not consume fruits, nuts, or animal-sourced foods. The Et-HEI showed an increasing trend in the probability of nutrient adequacy across quartiles except for vitamin B12, thiamine, vitamin C, calcium, and zinc. Women who completed high school and above had lower Et-HEI, also when adjusting for energy intake. The Et-HEI score was low, indicating the study population's consumption patterns had poor adherence to the Ethiopian FBDG. Low nutrient adequacies confirmed poor adherence to the FBDG. Ethiopia's current diet is lacking in both quantity and quality. Besides calcium and vitamin B12 in the fasting diet, it is possible to develop a feasible optimal diet for fasting and non-fasting women of reproductive age to meet their daily energy and nutrient requirements. Further adapting Ethiopian FBDG will help ensure that they are acceptable, understandable, culturally appropriate, and practical. A healthy diet costs twice as much as the current diet. Integrate FBDG into efforts to transform the food system, and ongoing research, monitoring, and evaluation of FBDG will aid in fully implementing the dietary guidelines. The Et-HEI is an important tool for monitoring and evaluating the impact of interventions that target the improvement of diets or reaching healthy diets.